Distinct local circuit properties of the superficial and intermediate layers of the rodent superior colliculus. (8th April 2014) - Phongphanphanee, Penphimon; Marino, Robert A.; Kaneda, Katsuyuki; Yanagawa, Yuchio; Munoz, Douglas P.; Isa, Tadashi
Abstract The superior colliculus (SC) is critical in localizing salient visual stimuli and making decisions on the location of the next saccade. Lateral interactions across the spatial map of the SC are hypothesized to help mediate these processes. Here, we investigate lateral interactions within the SC by applying whole‐cell recordings in horizontal slices of mouse SC, which maintained the local structure of the superficial (SCs) visual layer, which is hypothesized to participate in localizing salient stimuli, and the intermediate (SCi) layer, which is supposed to participate in saccade decision‐making. When effects of either electrical or chemical (uncaging of free glutamate) stimuli were applied to multiple sites with various distances from the recorded cell, a pattern of center excitation‐surround inhibition was found to be prominent in SCs. When the interactions of synaptic effects induced by simultaneous stimulation of two sites were tested, non‐linear facilitatory or inhibitory interactions were observed. In contrast, in the SCi, stimulation induced mainly excitation, which masked underlying inhibition. The excitatory synaptic effects of stimulation applied at remote sites were summed in a near linear manner. The result suggested that SCs lateral interactions appear suitable for localizing salient stimuli, while the lateral interactions within SCi are more suitable for faithfully accumulating subthreshold signals for saccadic decision‐making. Implementation of this laminar‐specific organization makes the SC a unique structure for serially processing signals for saliency localization and saccadic decision‐making.